Brugada syndrome and syncope: a practical approach for diagnosis and treatment. Issue 7 (15th July 2021) - Mascia, Giuseppe; Bona, Roberta Della; Ameri, Pietro; Canepa, Marco; Porto, Italo; Parati, Gianfranco; Crotti, Lia; Brignole, Michele
Abstract: Syncope in patients with Brugada electrocardiogram pattern may represent a conundrum in the decision algorithm because incidental benign forms, especially neurally mediated syncope, are very frequent in this syndrome similarly to the general population. Arrhythmic syncope in Brugada syndrome typically results from a self-terminating sustained ventricular tachycardia or paroxysmal ventricular fibrillation, potentially leading to sudden cardiac death. Distinguishing syncope due to malignant arrhythmias from a benign form is often difficult unless an electrocardiogram is recorded during the episode. We performed a review of the existing literature and propose a practical approach for diagnosis and treatment of the patients with Brugada syndrome and syncope.